Mobility in Central European Late Eneolithic and Early Bronze Age: femoral cross-sectional geometry - Sládek, Vladimír; Berner, Margit; Sailer, Robert (American journal of physical anthropology, 2006)
Some scholars explain the absence of settlements in the Bohemian and Moravian Late Eneolithic (Corded Ware archaeological culture) as a consequence of pastoral subsistence with a high degree of mobility. However, recent archaeological studies argued that the archaeological record of the Late Eneolithic in Central Europe exhibits evidence for sedentary subsistence with mixed agriculture, similar to the subsequent Early Bronze Age. Because the archaeological data do not allow us to address unambiguously the mobility pattern in these periods, we used cross-sectional analysis of the femoral midshaft to test mobility directly on the human skeletal record. The results of femoral midshaft geometry do not support a high degree of mobility in the Late Eneolithic in Central Europe. This conclusion is supported mainly by no significant differences in male groups between the Late Eneolithic and Early Bronze Age in mechanical robusticity and shape of the femoral midshaft, although Corded Ware males still exhibit the highest absolute mean values of the diaphyseal shape (I(A-P)/I(M-L)) ratio and antero-posterior second moment of area. However, Late Eneolithic females have significantly higher torsional and overall bending rigidity because of a significantly higher medio-lateral second moment of area. This finding cannot be directly linked with a higher degree of long-distance mobility for these females. A significant difference was also found in overall decrease of size parameters of the femoral midshaft cross section for one of the Early Bronze Age samples, the Wieselburger females. Since the decrease of size and mechanical robusticity for Wieselburger females does not correspond with the parameters of Early Bronze Age females, we can expect a mosaic pattern of changes during the Late Eneolithic and Early Bronze Age period, instead of a simple unidirectional (diachronic) change of the mechanical environment.
Keywords: History, Ancient; biomechanika; Femur; Cross-Sectional Studies; biologická evoluce; Analysis of Variance; Europe; sexuální faktory; Evropa; Biomechanical Phenomena; mužské pohlaví; průřezové studie; Biological Evolution; dějiny starověku; analýza rozptylu; multivariační analýza; věkové faktory; Multivariate Analysis; ženské pohlaví; Locomotion; Humans; Sex Factors; Bone Density; kostní denzita; Age Factors; femur; Female; lokomoce; lidé; Male